The Relationship between Body Mass Index and the Severity of Coronary Artery Disease in Patients Referred for Coronary Angiography - Anne B. Gregory; Kendra K. Lester; Deborah M. Gregory; Laurie K. Twells; William K. Midodzi; Neil J. Pearce (Cardiology Research and Practice)
Background and Aim. Obesity is associated with an increased risk of cardiovascular disease and may be associated with more severe coronary artery disease (CAD); however, the relationship between body mass index [BMI (kg/m2)] and CAD severity is uncertain and debatable. The aim of this study was to examine the relationship between BMI and angiographic severity of CAD. Methods. Duke Jeopardy Score (DJS), a prognostic tool predictive of 1-year mortality in CAD, was assigned to angiographic data of patients ≥18 years of age (N=8,079). Patients were grouped into 3 BMI categories: normal (18.5–24.9 kg/m2), overweight (25.0–29.9 kg/m2), and obese (≥30 kg/m2); and multivariable adjusted hazard ratios for 1-year all-cause and cardiac-specific mortality were calculated. Results. Cardiac risk factor prevalence (e.g., diabetes, hypertension, and hyperlipidemia) significantly increased with increasing BMI. Unadjusted all-cause and cardiac-specific 1-year mortality tended to rise with incremental increases in DJS, with the exception of DJS 6 (p<0.001). After adjusting for potential confounders, no significant association of BMI and all-cause (HR 0.70, 95% CI .48–1.02) or cardiac-specific (HR 1.11, 95% CI .64–1.92) mortality was found. Conclusions. This study failed to detect an association of BMI with 1-year all-cause or cardiac-specific mortality after adjustment for potential confounding variables.